Efektivitas Media Canva terhadap Minat dan Hasil Belajar IPA Siswa Kelas V SDN Bakaran Wetan 03 Pati - Sulistiyowati Sulistiyowati; Nur Fajrie; Sri Surachmi W (Departement of Mathematics Education, 2023)
The purpose of this study was to increase students' interest in learning and learning outcomes in science for Fifth Class students at SDN Bakaran Wetan 03. The research method was an experiment using the one shoot case study data collection method. The research results were as follows; 1) Students' interest in learning in pre-test was low 12 students or 52%, medium was 10 students or 43%, high is 1 student or 4%. 2) Student learning outcomes in pre-test students who had not completed, 13 students or 59% of students who achieve completeness are 10 students or 41%, in post-test students who have not completed are 2 students or 8%, students who achieve completeness are 21 students or 92%. The use of media was effective for increasing interest and learning outcsmes in science.The researcher hopes that Canva's media will attract students' attention so as to arouse interest in learning and lead to learning outcomes according to the specified criteria.